Psychopathology in 7‐year‐old children with familial high risk of developing schizophrenia spectrum psychosis or bipolar disorder – The Danish High Risk and Resilience Study ‐ VIA 7, a population‐based cohort study. Issue 2 (June 2018) - Ellersgaard, Ditte; Jessica Plessen, Kerstin; Richardt Jepsen, Jens; Soeborg Spang, Katrine; Hemager, Nicoline; Klee Burton, Birgitte; Jerlang Christiani, Camilla; Gregersen, Maja; Søndergaard, Anne; Uddin, Md Jamal; Poulsen, Gry; Greve, Aja; et al.
Abstract : This study aimed to compare the psychopathological profiles of children at familial high risk of schizophrenia spectrum psychosis (FHR‐SZ) or bipolar disorder (FHR‐BP) with population‐based controls. We used Danish nationwide registers to retrieve a cohort of 522 seven‐year‐old children of parents with schizophrenia spectrum psychosis (N=202), bipolar disorder (N=120) or none of these disorders (N=200). Psychopathology was assessed by reports from multiple informants, including children, parents and teachers. Lifetime DSM‐IV diagnoses were ascertained by blinded raters through the Schedule for Affective Disorders and Schizophrenia for School‐Age Children. The dimensional assessment of psychopathology was performed by the Child Behavior Checklist, the Teacher's Report Form, a modified version of the ADHD‐Rating Scale, the Test Observation Form, and the State‐Trait Anxiety Inventory for Children. Current level of functioning was evaluated using the Children's Global Assessment Scale (CGAS). The prevalence of lifetime psychiatric diagnoses was significantly higher in both FHR‐SZ children (38.7%, odds ratio, OR=3.5, 95% confidence interval, CI: 2.2‐5.7, p < 0.001) and FHR‐BP children (35.6%, OR=3.1, 95% CI: 1.8‐5.3, p < 0.001) compared with controls (15.2%). FHR‐SZ children displayed significantly more dimensional psychopathology on all scales and subscales compared with controls except for the Anxious subscale of the Test Observation Form. FHR‐BP children showed higher levels of dimensional psychopathology on several scales and subscales compared with controls, but lower levels compared with FHR‐SZ children. Level of functioning was lower in both FHR‐SZ children (CGAS mean score = 68.2; 95% CI: 66.3‐70.2, p < 0.0001) and FHR‐BP children (73.7; 95% CI: 71.2‐76.3, p < 0.05) compared with controls (77.9; 95% CI: 75.9‐79.9). In conclusion, already at the age of seven, FHR‐SZ and FHR‐BP children show a higher prevalence of a broad spectrum of categorical and dimensional psychopathology compared with controls. These results emphasize the need for developing early intervention strategies towards this vulnerable group of children.